2009
DOI: 10.1243/09544070jauto1236
|View full text |Cite
|
Sign up to set email alerts
|

Combustion characteristics of a single-cylinder spark ignition gasoline and ethanol dual-fuelled engine

Abstract: The requirements of reduced emissions and improved fuel economy led to the introduction of direct-injection (DI) spark ignition (SI) engines. A dual-fuel injection system (DI and port fuel injection (PFI)) was also used to improve engine performance at high-speed highload conditions. Ethanol is one of the several alternative transportation fuels considered for replacing fossil fuels such as gasoline and diesel. Ethanol offers high octane quality but with lower energy density than fossil fuels. This paper prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The ISHC and ISCO were increased when the ratio of the DI was increased. This might be a result of incomplete combustion due to fuel impingement, mixture quality deterioration and over cooling effect [14]. ISNOx was reduced with the increased DI ratio because of the charge cooling effect enhanced by direct injection and consequently the reduced combustion temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISHC and ISCO were increased when the ratio of the DI was increased. This might be a result of incomplete combustion due to fuel impingement, mixture quality deterioration and over cooling effect [14]. ISNOx was reduced with the increased DI ratio because of the charge cooling effect enhanced by direct injection and consequently the reduced combustion temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Dual fuel combustion has been investigated in recent years to exploit the potential applications of ethanol to spark ignition (SI) engines [10,11,12,13,14,15]. Kasseris E. and Heywood J.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ford's ongoing research engine -'Bobcat', will use the dualinjection strategy at higher compression ratios to achieve greater mechanical efficiencies [31]. Finally, Zhu and co-workers studied the combustion characteristics of a single cylinder engine equipped with a dual-injection strategy [32,33]. Their results showed that the indicated mean effective pressure (IMEP) decreases with increased DI fuelling, except for some instances when using gasoline PFI and E85 in DI.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the performance of combustion is improved significantly when EDI is used. Zhu et al 29 performed test on the effect of different ethanol-gasoline dual-injection strategies on the combustion characteristics, including GPI plus gasoline direct injection (GDI), GPI plus EDI, and ethanol port injection (EPI) plus GDI. The best performance of combustion is achieved with GPI plus EDI, and the indicated mean effective pressure (IMEP) increases by 2% under light load compared with other dual-injection strategies.…”
Section: Introductionmentioning
confidence: 99%